From resources to reserves: a real option approach to quarry mining in the Aimasi River, West Papua - Setiawan, Arif; Hutapea, Ricardo O. M. (Journal of Degraded and Mining Lands Management, 2026)
The Aimasi River in West Papua contains substantial sand and gravel deposits with potential for quarry development. While previous assessments emphasized geological aspects, their economic feasibility has not been systematically examined. This study applied Net Present Value (NPV) and Real Options Analysis (ROA) to evaluate the viability of investments and their implications for converting resources into reserves. The NPV of the proposed project is USD 5,915.56, which is considerably lower than the option value of deferring the investment for one year (USD 116,197.59). Extending the decision horizon from one to three years raises the option value from USD 61,650.15 to USD 116,197.59. Several nodes yield positive payoffs, supporting immediate investment (classified as proved reserves) or deferral (classified as probable reserves), while nodes with zero payoffs are more appropriately classified as resources. These findings demonstrate the value of ROA in bridging geological potential and economic feasibility, thereby strengthening the framework for resource-to-reserve conversion in small-scale quarry mining.